THE INFLUENCE OF PROFITABILITY, CAPITAL STRUCTURE, INVESTMENT DECISION, AND FIRM SIZE ON FIRM VALUE (A Study in the Pharmaceutical Sector Listed on the Indonesian Stock Exchange) - Chairil Akhyar; Hepi Boang Manalu; Husaini; Wardhiah (Journal of Accounting Research, Utility Finance and Digital Assets, 2023)
This study examines the influence of profitability, capital structure, investment decisions, and firm size on firm value in pharmaceutical sub-sector companies on the Indonesia Stock Exchange. This study uses secondary data from the financial statements of each pharmaceutical sub-sector company. The sample in this study consists of 9 pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange during 2018-2021. The data analysis method used is a multiple linear regression test with the help of Eviews 12. The results partially show that return on assets, return on equity, and capital structure has a positive and significant effect on firm value. Meanwhile, investment decisions and firm size partially do not significantly affect firm value in pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange for the 2018-2021 period.